OP0016 Comparative effectiveness at 1 year of different ANTI-TNF drugs as first biologic dmard in patients with rheumatoid arthritis – results from the nationwide swedish register. (15th June 2017) - Turesson, C; Frisell, T; Dehlin, M; Giuseppe, D Di; Feltelius, N; Kastbom, A; Askling, J
Abstract : Background: Treatment with TNF inhibitors is part of the management of patients with severe rheumatoid arthritis (RA). There is limited data on the comparative effectiveness of different TNF inhibitors from clinical trials and observational studies of patients treated in clinical practice. Objectives: To compare effectiveness of different TNF inhibitors in a large, population representative, sample of bionaïve patients with RA. Methods: The study was based on the Swedish Rheumatology Quality register, in which clinical data are prospectively recorded at treatment initiation and at subsequent visits. Patients with RA initiating a TNF inhibitor as their first ever biologic DMARD in 2010–2014 were included and followed through 2015. The proportion remaining on drug at 1 year (±90 days) after starting therapy was compared. Furthermore, effectiveness at 1 year was assessed as the proportions with EULAR good response, remission (DAS28 <2.6), HAQ improvement (>0.2) and swollen and tender joint counts of 0, all corrected for drug survival (1). The relative response was estimated with log-binomial regression, adjusting for potential confounders and using the largest group (etanercept) as reference. Results: A total of 5568 patients were included. There was a significant difference in the adjusted chance of drug survival across TNF inhibitors (Table). Patients treated with certolizumab or infliximab were less likely to remain on treatment compared to those started on etanercept. The chance of achieving each of the clinical response measures was significantly lower for those initiating infliximab compared to patients treated with etanercept. There were no significant differences in these outcomes compared to etanercept for any of the other TNF inhibitors. Conclusions: Patients with RA starting infliximab as their first biologic DMARD were less likely to remain on treatment with significant improvement at 1 year compared to those initiating etanercept. There was a similar trend for certolizumab vs. etanercept, but there were no consistent differences in clinical effectiveness between etanercept and adalimumab or golimumab. Treatment context may affect these patterns. References: Kristensen A&R 2006; 54: 600–6. Disclosure of Interest: C. Turesson Grant/research support from: Abbvie, Pfizer, Roche, Consultant for: MSD, Pfizer, Roche, Paid instructor for: Abbvie, Bristol-Myers Squibb, Janssen, MSD, Pfizer, Roche and UCB, T. Frisell: None declared, M. Dehlin: None declared, D. Di Giuseppe: None declared, N. Feltelius: None declared, A. Kastbom Consultant for: Bristol-Myers Squibb, Pfizer, Roche, UCB, Paid instructor for: Bristol-Myers Squibb, Pfizer, Roche, UCB, J. Askling Grant/research support from: Abbvie, UCB, Pfizer, Merck, Samsung, Roche, Lilly